Research on the Corrosion Damage Mechanism of Concrete in Two Freeze–Thaw Environments - Xianhua Yao; Min Zhang; Junfeng Guan; Lielie Li; Weifeng Bai; Zepeng Liu (Advances in Civil Engineering)
This study aims to investigate the effects of two freeze–thaw environments (i.e., maintenance freeze-thaw (MFT) environment and immersion freeze-thaw (IFT) environment) on the durability performance, deterioration rules, and mechanisms of concrete. In MFT, the concrete specimens were firstly cured in the standard curing environment (temperature, 20 ± 3, humidity, not less than 95%, and ages, 28 d) and then were carried out in freeze–thaw environment, while in IFT, the concrete specimens were firstly cured in the salt (NaHCO3, NaCl, and Na2SO4) immersion environment for 90 d and then were carried out in freeze–thaw environment. In this study, the damage features, relative dynamic elastic modulus, mass changes, and erosion-resistance coefficient of concrete have been measured. Thereafter, using the scanning electron microscopy (SEM) and the mercury intrusion porosimetry (MIP), the air-void structure parameters and the microstructures have been measured, respectively. The results show that the relative dynamic elastic modulus and the erosion-resistance coefficient of the compressive strength of the concrete in the IFT environment are, respectively, 14.3% and 21.0% higher than those of the concrete in the MFT environment. In addition, the results of the microstructure analyses show that the corrosion damages of the concrete are mainly caused by the combined action of the corrosion products of ettringite and freeze–thaw environment. However, the damage to the concrete in the MFT environment is more serious than that in the IFT environment. The results of the MIP analysis show that the harmful pore value for the concrete in the MFT environment is almost two times larger than that for the concrete in the IFT environment.